ARE LICHEN GROWTH FORM CATEGORIES SUPPORTED BY CONTINUOUS FUNCTIONAL TRAITS: WATER-HOLDING CAPACITY AND SPECIFIC THALLUS MASS?. (6th March 2020) - Wan, S.; Ellis, C. J.
Abstract : The focus of community ecology has shifted from the description of taxonomic composition towards an understanding of community assembly based on species' 'functional traits'. The functional trait approach is well developed for vascular plants, utilising variability of continuous phenotypic characters that affect ecological fitness, such as specific leaf area, tissue nitrogen concentration or seed mass, to explain community structure. In contrast, community assembly studies for poikilohydric cryptogamic plants and fungi, such as lichens, remain focused on broad categorical traits such as growth form difference: fruticose, foliose or crustose. This study examined intra- and interspecific variability for two highly promising continuous phenotypic measurements that affect lichen physiology and ecological fitness: water-holding capacity (WHC) and specific thallus mass (STM). Values for WHC and STM were compared within and among species, and within and among key macrolichen growth forms (fruticose and green-algal and cyanolichen foliose species), asking whether these widely used categories adequately differentiate the continuous variables (WHC and STM). We show large intra- and interspecific variability that does not map satisfactorily onto growth form categories, and on this basis provide recommendations and caveats in the future use of lichen functional traits.